Pengaruh Model Brain Based Learning Berbantuan E-Learning Terhadap Minat Belajar Peserta Didik - Hajati, Kartika; Nuryadin, Andi Rosman; Nabila, Nurul Lailatul (Universitas PGRI Semarang, 2023)
This study aims to determine the effect of the e-learning-assisted Brain Based Learning model on students' learning interest. Information obtained by the teacher regarding students' learning interests and the learning model applied in this study and the results, helps teachers to carry out learning interventions that suit the needs of students. This is the teacher's effort to guide students, in this case tutoring to be able to develop their potential optimally. In addition, it can encourage students to understand themselves and their learning environment, so that they are helped to optimize the learning outcomes achieved. The research design used was a quasi-experiment with a nonequivalent control group design. The purposive sampling technique was used to determine which research subjects were included, as many as 65 people, consisting of 31 students in the experimental group and 34 students in the control group. The instruments used were a questionnaire of interest in learning and an observation sheet of the implementation of the learning model. Data were analyzed using descriptive and inferential statistical tests, namely through the t-test, the sig value was obtained. (2-tailed) smaller than 0.05 (0.000 0.05), it can be concluded that Ha is accepted and Ho is rejected. Based on these results, it shows that there is a significant effect of the use of e-learning assisted brain-based learning models on student's physical learning interests.